Schichtlinien und Kanten-Zeichnung: Neue Methode der Geländedarstellung auf der Topographisch-morphologischen Kartenprobe 1:25 000 Alpiner Karst am Hohen Ifen - Brandstätter, Leonhard (ERDKUNDE, 1960)
The research group “topographic-morphological map samples, under the chairmanship of Prof. R. Finsterwalder, has set itself the task of preparing and publishing 30 map samples of selected characteristic landscapes for Middle Europe on a scale of 1:25,000 in the most progressive way possible in order to contribute to the development of the most important of the major German map series. The bulk of the work is carried out by the survey offices of the West German Lander, but university departments, the national survey offices of Austria and Switzerland, the Alpenverein and others have also been invited to contribute. Because of this, the author of the paper, a privately working cartographer, can make a practical suggestion for an improvement of relief representation on the modern 1:25,000 contour map. A glance at the development of relief representation on 1:25,000 maps shows that up till now the too traditional methods of representation have impeded full use being made of the potentialities provided by the present exact photogrammetric survey methods. In the included map sample of the Hohe Ifen mountain group, which is based on a photogrammetric survey, it can quite clearly be seen that while the representation of the landforms by using exact contour lines gains geometrically, it suffers greatly pictorially. To omit the exact contour lines when preparing the relief drawing of a map is out of the question on the grounds of optimum geometrical presentation. Thus a method of presentation must be found which can also make use of the exact contour Lines for pictorial presentation. In this connexion two main demands arise: 1. The contour lines should, by means of an even contour interval, provide an optimum base for relief representation. This can only be achieved if the contour interval is chosen according to the type of relief to be represented. The resulting regional contour lines show quite obviously a neutral three-dimensional arrangement. Chosen in that way, contour lines provide the best pictorial representation of which they are capable. All other map contents should be chosen bearing in mind the relative closeness of the contour lines and care must be taken in particular to avoid im pairing the ease of legibility of the contour lines by representation of vegetation or rocks. 2. Nevertheless on breaks of slope contour lines fail to represent relief adequately according to its characteristic appearance. These gaps in representation are not merely of a pictorial kind, they are also of a geometrical character. In all cases they concern relief features which in size are less than the contour interval of which, because of their irregular shape, do not permit an interpolation of straight or slightly curved form lines. In order to close these gaps the contour lines must be supplemented by additional drawings to take care of these curves which otherwise escape representation. The suggested kantographic method, based on the work of Prof. R. Lucerna, attemps to do justice to these demands with a minimum of additional drawing effort. Its single purpose is to overcome the weakness inherent in the representation of relief by con tour lines only. Thus no confusing ambiguities between contour lines and kantographic lines result. As additional methods to supplement landform representation by contour lines, the two following seem ad visable: the characterisation of the ground structure by symbols with as little weight as possible, and the emphasizing of major sudden changes in the terrain, as for instance plateau edges, by strips of hill shading. As the enclosed map shows, the method as discussed above results in an easily legible and morphologically sound representation which geometrically as well as pic torially provides sufficient information. In particular it may be noted that not only is the greatly broken up area of bare rock shown with a characteristic drawing, but that similarly broken up ground covered by vegetation is shown in the same way. The so far usual methods of representing the topography of cultivated land are unsatisfactory largely because no means of bringing out breaks of slope have been considered. There has been increasing demand to overcome this deficiency and the map samples men tioned initially, most of which have been charged with problems of representing cultivated land, clearly show that progress in being made first and foremost in that respect. In the opinion and based on the practical, experience of the author, the method Contour lines and kantography provides the means for a clear and satisfactory representation of any type of terrain on any scale used for topographic maps without a major effort.